Improvement of the Solubility of the Vp2 Hypervariable Region of Infectious Bursal Disease Virus by Fusion to the NP Protein of Newcastle Disease Virus - Saadun, Rafidah (2005)
Infectious bursal disease virus (IBDV) has five proteins, VP1, VP2, VP3, VP4 and VP5. The VP2 protein is the major host-protective immunogen of IBDV. The hypervariable region (HVR) of the VP2 protein [VP2(HVR)] elicits neutralising antibodies. The coding sequence of the VP2(HVR) was amplified by polymerase chain reaction (PCR) and ligated to the 3’ end of the NP gene of Newcastle disease virus (NDV). The NP-VP2(HVR) fusion protein was produced under the control of trc promoter in the bacterial expression vector, pTrcHis2, for intracellular expression in Escherichia coli TOP 10 cells. The NP-VP2(HVR) was expressed as a 75 kDa fusion protein containing the myc epitope and His-tag at its C-terminal end. However, most of the fusion proteins produced in the cell existed as insoluble inclusion bodies. Thus , the NP-VP2(HVR) region was then sub-cloned into pRSETA and pET-43.1(a) expression vectors which contain the T7 promoters. The recombinant plasmids were then introduced into E. coli BL 21 (DE3), BL 21 (SI) dan Origami B cells respectively. The yields of the NP-VP2(HVR) fusion protein produced by the different vectors in the respective E. coli strains were compared. Although the levels of protein expression still remained the same in the various E. coli strains, the solubility of the NP-VP2(HVR) fusion proteins improved significantly in BL 21 (DE3), BL 21 (SI) and Origami B cells from 80% to 97%. The development of these fusion systems will be useful as an alternative strategy in protein solubilization.